Study of phenoxy radical couplings using the enzymatic secretome of Botrytis cinerea - Huber, Robin; Marcourt, Laurence; Félix, Fabien; Tardy, Sébastien; Michellod, Emilie; Scapozza, Leonardo; Wolfender, Jean-Luc; Gindro, Katia; Queiroz, Emerson Ferreira (Frontiers in Chemistry, 2024)
Phenoxy radical coupling reactions are widely used in nature for the synthesis of complex molecules such as lignin. Their use in the laboratory has great potential for the production of high value compounds from the polyphenol family. While the enzymes responsible for the generation of the radicals are well known, the behavior of the latter is still enigmatic and difficult to control in a reaction flask. Previous work in our laboratory using the enzymatic secretome of B. cinerea containing laccases has shown that incubation of stilbenes leads to dimers, while incubation of phenylpropanoids leads to dimers as well as larger coupling products. Building on these previous studies, this paper investigates the role of different structural features in phenoxy radical couplings. We first demonstrate that the presence of an exocyclic conjugated double bond plays a role in the generation of efficient reactions. In addition, we show that the formation of phenylpropanoid trimers and tetramers can proceed via a decarboxylation reaction that regenerates this reactive moiety. Lastly, this study investigates the reactivity of other phenolic compounds: stilbene dimers, a dihydro-stilbene, a 4-O-methyl-stilbene and a simple phenol with the enzymatic secretome of B. cinerea. The observed efficient dimerization reactions consistently correlate with the presence of a para-phenol conjugated to an exocyclic double bond. The absence of this structural feature leads to variable results, with some compounds showing low conversion or no reaction at all. This research has allowed the development of a controlled method for the synthesis of specific dimers and tetramers of phenylpropanoid derivatives and novel stilbene derivatives, as well as an understanding of features that can promote efficient radical coupling reactions.